The status of spermatogenesis in germ cell tumor bearing testis and its association with metastatic disease - Çulpan, Meftun; Yıldırım, Asıf; Özkanlı, Sıdıka Şeyma; Sobay, Resul; Gürsoy, Fatıma; Topaktaş, Ramazan; Gümrükçü, Gülistan; Görgel, Sacit Nuri; Çakalağaoğlu, Fulya; Çil, Gökhan; Özsoy, Şule; Günel, Hümeyra; et al. (My University, 2024)
Introduction: We aimed to evaluate the status of spermatogenesis detected by histological examination of non-tumoral testicular tissues in tumor bearing testis and its association with advanced stage disease. Patients and Methods: We retrospectively reviewed patients with testicular germ cell tumors (TGCTs) that undergone radical orchiectomy. All non-tumoral areas of the orchiectomy specimens were examined for the status of spermatogenesis. Patients were divided into two groups as localized (stage I) and metastatic (stage II-III) disease and analyzed separately for seminomatous (SGCT) and nonseminomatous germ cell tumors (NSGCT). Results: Four hundred fifty-four patients were included in our final analysis. Of those, 195 patients had SGCT, and 259 patients had NSGCT. Three hundred and six patients had localized disease at the time of diagnosis. Median (Q1-Q3) age was 31 (26 – 38) years and 102 (22.5%) patients had normal spermatogenesis, 177 (39.0%) patients had hypospermatogenesis and 175 (38.5%) patients had no mature spermatozoa. On multivariate logistic regression analysis, embryonal carcinoma >50% (1.944, 95 %CI 1.054-3.585, P = .033) and spermatogenesis status (2.796 95% CI 1.251-6.250, P = .012 for hypospermatogenesis, and 3.907, 95% CI 1.692-9.021, P = .001 for absence of mature spermatozoa) were independently associated with metastatic NSGCT. However, there was not any variables significantly associated with metastatic SGCT on multivariate logistic regression analysis. Conclusion: Our study demonstrated that only 22.5% of patients with TGCTs had normal spermatogenesis in tumor bearing testis. Impaired spermatogenesis (hypospermatogenesis or no mature spermatozoa) and predominant embryonal carcinoma are associated with advanced stage NSGCT.
Keywords: Metastasis; Nonseminomaatous; Orchiectomy; Seminoma; Testicular Cancer